Analysis of DNA of higher primates using inter-SINE PCR - Ryabinina, N. L; Bannikova, A. A; Sheremet'eva, V. A; Chikobava, M. G; Lapin, B. A; Kramerov, D. A (Russian journal of genetics, 2008)
Two types (MIR and Alu) of short interspersed repeated DNA sequences (SINEs) were used for analysis of genetic relationships among higher primates, and for detection of polymorphism in human genomic DNA. The DNA regions located between the neighboring copies of these SINEs were amplified in polymerase chain reaction with primers complementary to the MIR and Alu consensus sequences (inter-SINE PCR). Comparison of the sets of amplified DNA fragments for different species or individuals provides evaluation of the relationships among them. Using inter-MIR PCR technique, the relationships among the higher primates of the infraorder Catarrhini reported elsewhere were confirmed, pointing to the efficiency of the method for phylogenetic studies. No human DNA polymorphism was revealed with the help of inter-MIR PCR. This polymorphism was detected by means of inter-Alu PCR, which is probably associated with the continuing amplification of Alu elements in human genome.